Impact of Credit Risk Management on the Performance of Selected Nigerian Banks - Nwude, E. Chuke; Okeke, Chinedu (International Journal of Economics and Financial Issues, 2018)
This study investigated the impact of credit risk management on the performance of deposit money banks in Nigeria using five banks that had highest asset base. Ex-post facto research design was adopted using dataset for the period 2000 to 2014 collated from the annual reports and financial statement of the selected deposit money banks. Three hypotheses were proposed and tested using ordinary least square (OLS) regression model. The findings reveal that credit risk management had a positive and significant impact on total loans and advances, the return on asset and return on equity of the deposit money banks. The study recommended that bank managers need to put more efforts to control the NPL by critically evaluating borrowers’ ability to pay back. The regulator should strengthen its monitoring capacity in this regard. Keywords: credit risk, bank performance, risk management, return on equity, return on asset, non-performing loans. JEL Classifications: G21, G32